Modulation of the dynamics and cellularity of adipose tissues in different fat depots in broilers by dietary dexamethasone - Sultana, Nasrin; Islam, Rafiqul (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The objective of this investigation was to determine the effects of dexamethasone (DEX) on the weight and cellularity of abdominal and subcutaneous fat depots. Materials and Methods: The study was conducted on four broiler chicks (20 chicks per group) fed commercial feed and water ad libitum. The DEX was supplied with feed at 0 mg/kg (non-DEX), 3 mg/kg (DEX-1), 5 mg/kg (DEX-2), and 7 mg/kg (DEX-3) from day 0 to day 28. The entire abdominal and subcutaneous fat depots were collected and weighed after sacrificing five birds from each group on days 14 and 28. Results: The DEX groups had considerably lower (p < 0.05) fat depot weights with dose-related variation noted among the DEX groups. The histological findings revealed the presence of unilocular, round to oval-shaped adipocytes. The DEX-1 and DEX-2 had way lower (p < 0.05) numbers of adipocytes while the DEX-3 had considerably higher (p < 0.05) numbers of adipocytes than the non-DEX. DEX-1 and DEX-2 had larger (p < 0.05) adipocytes whereas DEX-3 had smaller adipocytes than the non-DEX. Adipocyte sizes and fat depot weights were found to have very strong negative relationships. Conclusion: Dietary DEX affects the growth and distribution of abdominal and subcutaneous fat depots and adipocyte cellularity subjected to both dose and duration of DEX treatment. J. Adv. Vet. Anim. Res., 9(4): 583–590, December 2022 http://doi.org/10.5455/javar.2022.i627